Comparative study in clinical response in open versus laparoscopic ventral hernia repair - Sayyad, Sohail T.; Ilyas, Mohammad; Satyanarayana, G.; H., Yashaswini (International Surgery Journal, 2016)
Background: Repair of ventral hernia is one of the most common operations performed by surgeons around the world. The treatment of this common problem has seen an evolution from the pure tissue repairs to the prosthetic repairs and in the recently to laparoscopic repair. The fact that so many hernia repairs are practiced is a testimony to the fact that probably none is distinctly superior to the other. Hence this comparative study of clinical response in open versus laparoscopic ventral hernia repair in terms of operative time, post-operative pain, hospital stay and time until resumption of daily and routine work. Methods: In this prospective observational study, 40 patients of uncomplicated ventral hernia were scheduled to undergo elective hernia repair, 20 patients by open mesh repair (onlay method) and 20 by laparoscopic mesh repair. Complicated and recurrent hernias were excluded. Patients were followed up with regular visits at 3 months interval till 1 year. Results: Laparoscopic hernia repair requires longer time to perform compared to open repair. Postoperative pain and analgesic requirement were significantly less in laparoscopic group after 24 hours of surgery. Overall complications were more common in open group as compared to laparoscopic group. There is significant reduction in hospital stay, return to daily and normal activities in patients underwent laparoscopic hernia repair. Conclusions: The database of our retrospective study regarding age and sex incidence, clinicopathological features and therapeutic outcome was comparable to other studies in various literatures.